2018
DOI: 10.1080/14647273.2018.1432078
|View full text |Cite
|
Sign up to set email alerts
|

The association between trans fatty acids, infertility and fetal life: a review

Abstract: Trans fatty acids (TFAs) are thought to affect reproductive health by causing adverse effects on sperm morphology and ovum quality as a result of changing membrane lipid composition which, in turn, leads to impairment in metabolic pathways. This literature review examines the evidence for the effects of dietary TFAs on male and female infertility. Studies conducted between 2007 and 2017 on the effect of dietary TFAs on human reproductive health and fetal life have been included. They indicate that TFA intakes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Opposite to PUFAs, trans-FAs and SFAs appeared to have an effect on spermatogenesis. The association between trans-FAs, infertility, and fetal life has been reviewed by Çekici and Akdevelioğlu [108]. trans-FAs are found in commercially baked and fried foods, which accumulate in the testis, and high consumption is related to poor semen quality [33].…”
Section: Spermatozoa Fatty Acids and Dietmentioning
confidence: 99%
“…Opposite to PUFAs, trans-FAs and SFAs appeared to have an effect on spermatogenesis. The association between trans-FAs, infertility, and fetal life has been reviewed by Çekici and Akdevelioğlu [108]. trans-FAs are found in commercially baked and fried foods, which accumulate in the testis, and high consumption is related to poor semen quality [33].…”
Section: Spermatozoa Fatty Acids and Dietmentioning
confidence: 99%
“…The fact that certain dietary ingredients are deemed responsible for male and female infertility makes it crucial to study the effects of nutrition on infertility and reproductive health. Especially trans fatty acids have adverse effects on male and female reproductive health, cause abnormalities in certain metabolic pathways and damage the metabolism of essential components of the reproductive system [5,6]. When other nutritional factors that may be responsible for infertility are evaluated; saturated fat, red meat, processed meats, fatty dairy products, sugar and sweeteners, alcohol and caffeine come to the forefront.…”
Section: Commentarymentioning
confidence: 99%
“…Many factors can affect the asthenospermia including fibrous sheath, cilium, energy metabolism, calcium channel and essential fatty acids [ 3 , 4 , 5 ]. However, in this study, we found that SMS2 was related with asthenospermia.…”
Section: Discussionmentioning
confidence: 99%
“…However, asthenospermia, which is associated with poor sperm viability and motility, is the leading factor in male infertility [ 1 , 2 ]. Many causes of asthenospermia have been reported so far [ 3 , 4 , 5 ], which include dysplasia of fibrous sheath, defects in the action of cilium, disfunction of energy metabolism, dysplasia of calcium channel [ 3 , 4 ]. Insufficiency of essential fatty acid, such as DHA, is also a cause of this disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation